A new linear adjacency approach for facility layout problem with unequal area departments. (October 2015) - Ghassemi Tari, Farhad; Neghabi, Hossein
Highlights: A new general and widespread definition for adjacencies between departments is presented. The proposed definition can be converted to classical definition, easily. Useful recommendation for determination of new parameter is stated. A new linear mixed integer program is presented. Abstract: In this study a new version of adjacency, which provides a more flexible layout design, is proposed. In the proposed version, departments which are nonadjacent yet close to each other are considered to be adjacent with a smaller adjacency rating. It is shown that the proposed adjacency is a generalized version of the traditional adjacency. A mathematical programming model is developed for the proposed facility layout problem. To show the flexibility and efficacy of the proposed model, a computational study is conducted. The solution of an illustrative example as well as the solutions of several test problems, reveal flexibility and efficacy of the proposed model.